2015
DOI: 10.1021/acs.joc.5b00853
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Small 3-Fluoro- and 3,3-Difluoropyrrolidines Using Azomethine Ylide Chemistry

Abstract: Here, we report accessing small 3-fluoropyrrolidines and 3,3-difluoropyrrolidines through a 1,3-dipolar cycloaddition with a simple azomethine ylide and a variety of vinyl fluorides and vinyl difluorides. We demonstrate that vinyl fluorides within α,β-unsaturated, styrenyl and even enol ether systems can participate in the cycloaddition reaction. The vinyl fluorides are relatively easy to synthesize through a variety of methods, making the 3-fluoropyrrolidines very accessible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…[11] In the present study,w ew anted to extend this strategy towards other spirocycles. In fact, all three-(5, 6), four-(2, 7-10), five- (11)(12)(13), six-(4, [14][15][16][17][18][19][20], and seven-membered-ring (21)a lkenes gave the desired spirocyclic products in good to excellent yields. Only startingm aterial wasr ecovered from the reactionm ixture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] In the present study,w ew anted to extend this strategy towards other spirocycles. In fact, all three-(5, 6), four-(2, 7-10), five- (11)(12)(13), six-(4, [14][15][16][17][18][19][20], and seven-membered-ring (21)a lkenes gave the desired spirocyclic products in good to excellent yields. Only startingm aterial wasr ecovered from the reactionm ixture.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] Recently,o ur group, and Juhl and co-workers, have independently developedar apid two-step approacht os pirocyclic pyrrolidines from four-membered-ring aliphatic ketones. [11][12][13] Three-and six-membered-ring (hetero)aliphatic cyclic alkenes have also been used previously, but very rarely and not systematically.T ot he best of our knowledge,c yclopropyl-containings ubstrates have been mentioned in only one patent, [14] whereas six-membered-ring (hetero)aliphatic substrates have received somewhat more attention. [11][12][13] Three-and six-membered-ring (hetero)aliphatic cyclic alkenes have also been used previously, but very rarely and not systematically.T ot he best of our knowledge,c yclopropyl-containings ubstrates have been mentioned in only one patent, [14] whereas six-membered-ring (hetero)aliphatic substrates have received somewhat more attention.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Genung and co-workers from Pfizer developed this two-step transformation into a one-pot methodology for the formation of 2-substituted indazoles. 35 This concerted cycloaddition reaction can be used with a range of fluorinated olefins including, enol ethers, α,β-unsaturated esters, heteroaromatics, as well as electron-deficient and electron-rich styrene analogues. Both electron-rich and electron-poor ortho-nitrobenzaldehydes were shown to successfully undergo reaction with substituted anilines, aminopyridines, and aliphatic amines.…”
Section: Selectivity In Heterocycle Formationmentioning
confidence: 99%
“…McAlpine group [22] showed that vinyl difluorides could participate in 1,3-dipolar cycloaddition with a simple azomethine ylide to generate gem-difluoropyrrolidines. They tried to synthesize 2,2-difluorostyrenes with benzaldehydes and Hu's reagent, then found out that benzaldehydes with electron deficient groups gave higher yields in [3+2] cycloaddition reactions (Scheme 16).…”
Section: Scheme 15 Julia-kocienski Reaction Of Aliphatic Aldehydesmentioning
confidence: 99%